2020
DOI: 10.1038/s42003-020-01220-9
|View full text |Cite
|
Sign up to set email alerts
|

Context dependent effects of ascorbic acid treatment in TET2 mutant myeloid neoplasia

Abstract: Loss-of-function TET2 mutations (TET2MT) are common in myeloid neoplasia. TET2, a DNA dioxygenase, requires 2-oxoglutarate and Fe(II) to oxidize 5-methylcytosine. TET2MT thus result in hypermethylation and transcriptional repression. Ascorbic acid (AA) increases dioxygenase activity by facilitating Fe(III)/Fe(II) redox reaction and may alleviate some biological consequences of TET2MT by restoring dioxygenase activity. Here, we report the utility of AA in the prevention of TET2MT myeloid neoplasia (MN), clarify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 60 publications
5
26
0
Order By: Relevance
“…Likewise, our group confirmed that long-term AA treatment prevented MN evolution in Tet2-deficient murine models [17]. However, TET2 loss due to catalytic domain lysine acetylation or missense mutations prevented this beneficial effect, which was restored by the additional use of class I and II histone deacetylase inhibitors [17]. Lower than normal AA levels have been found in patients with MN, and AA has been used at supraphysiological doses in a case of TET2 mutant AML, confirming its potential therapeutic role in TET2-mutant MN [48].…”
Section: Tet2 As An Actionable Targetsupporting
confidence: 67%
See 2 more Smart Citations
“…Likewise, our group confirmed that long-term AA treatment prevented MN evolution in Tet2-deficient murine models [17]. However, TET2 loss due to catalytic domain lysine acetylation or missense mutations prevented this beneficial effect, which was restored by the additional use of class I and II histone deacetylase inhibitors [17]. Lower than normal AA levels have been found in patients with MN, and AA has been used at supraphysiological doses in a case of TET2 mutant AML, confirming its potential therapeutic role in TET2-mutant MN [48].…”
Section: Tet2 As An Actionable Targetsupporting
confidence: 67%
“…Moreover, AA was able to restore 5-hmC formation, drive DNA hypomethylation and expression of a TET2 gene signature, and ultimately suppressed leukemia progression in patient-derived xenografts (PDXs) [47]. Likewise, our group confirmed that long-term AA treatment prevented MN evolution in Tet2-deficient murine models [17]. However, TET2 loss due to catalytic domain lysine acetylation or missense mutations prevented this beneficial effect, which was restored by the additional use of class I and II histone deacetylase inhibitors [17].…”
Section: Tet2 As An Actionable Targetsupporting
confidence: 57%
See 1 more Smart Citation
“…Consistently, in acute myeloid leukemia (AML) cells with TET2 mutations, treatment with vitamin C mimicked TET2 restoration by increasing TET activity ( Figure 4 ) and blocked leukemia progression in patient-derived tumor xenograft models [ 102 ]. However, the ability of vitamin C to restore TET2 activity seems to depend on N- and C-terminal lysine acetylation and type of TET2 mutations [ 103 ].…”
Section: Mechanisms Of Vitamin C Anticancer Actionmentioning
confidence: 99%
“…In particular, it has been shown that interleukin-1β upregulates the expression of P-selectin in endothelial cells, a known chemo-attracting agent for monocytes, currently evaluated as a possible actionable target in the setting of CHIP and MDS to decrease cardiovascular risk [ 68 , 69 ]. Another approach currently in evaluation is the use of vitamin C, taking into account the recent data on its role in restoring some TET2 functions [ 70 , 71 ]. However, as discussed, a growing body of evidence regarding the underlying link between CHIP and increased cardiovascular risk points towards the presence of deregulated inflammation, providing favorable conditions for the CHIP clone(s) to expand and produce hyper-inflammatory leukocytes/monocytes, ultimately leading to cardiovascular events [ 72 ].…”
Section: Clinical Implications Of Chip: a Focus On Cardiovascular mentioning
confidence: 99%